Public diplomacy and related concepts from the perspective of Lasswell’s communication model - Saliu, Hasan (Array, 2020)
The purpose of this article is to explore the differences between public diplomacy and similar concepts that relate to the country’s international image. Concepts such as public diplomacy, traditional diplomacy, foreign policy, international public relations, propaganda, national branding, etc., are often seen as synonymous. A mere observation of these concepts is provided in the literature review. These concepts are elaborated based on the communication actors’ perspective, the inter-communicating parties, the message providers, the message recipients, and the mode of communication, whereas identifying the differences and distinctions between them is realized according to the Lasswell communication formula. The conclusions show that this communication approach provides more potential to identify the differences between these concepts as compared to the current approaches, which view them from an interdisciplinary perspective.